Smart Campus: Desain dan Implementasi Sistem Monitoring dan Kontrol Lampu dan AC - Afis Asryullah Pratama; Reza Putra Pradana; Arvita Agus Kurniasari; Ahmad Fahriyannur Rosyady; Dwi Putro Sarwo Setyohadi (bit-Tech, 2026)
The rapid growth of information and communication technology (ICT) has improved many aspects of community life, including access to information, productivity, and innovation. However, the widespread use of digital devices also increases energy consumption due to technological infrastructure and inefficient user behavior, such as leaving equipment powered on when not in use. While technological development can support energy efficiency, developing new energy systems requires complex research. Automation through the Internet of Things (IoT) offers a more practical solution for energy management. In the educational sector, the smart campus concept represents the digital transformation of campus infrastructure to improve operational efficiency and user comfort. This study aims to design and implement a practical, localized, secure, highly interconnected, and scalable monitoring and control system for lights and air conditioners within a campus environment. The system was developed by reviewing previous studies, evaluating available hardware, selecting appropriate network architectures and communication protocols, implementing IoT devices, and integrating them with a server platform. The system utilizes Zigbee communication and a local MQTT broker with authentication to ensure secure and reliable connectivity. Using devices from multiple manufacturers enables interoperability and vendor independence, while scalability is achieved through simple device installation and pairing. Experimental results show reliable performance with response times of 1–3 seconds without errors. Automation features allow lights and air conditioners to activate before working hours and turn off automatically at night if left on, improving energy efficiency and convenience in a smart campus environment.